UJI AKTIVITTAS ANTIFUNGI EKSTRAK ETANOL UMBI BAWANG MERAH (Allium cepa L.) TERHADAP Candida albicans DAN Pityrosporum ovale - Helen Anjelina Simanjuntak; Megawati Butar - Butar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2019)
Candida albicans dan Pityrosporum fungal caused micosis infections such as candidiasis and dandruff. The altervative medicine as antifungal bioactive substance is obtained from Bulbus Allium cepa L. exstract. The ekstraction of Bulbus Allium cepa L. has held by maserasi technic using etanol 96% as a solvent. The phytochem skrining result of the Bulbus Allium cepa L. extract is composed by alkaloid, flavanoid, tannin, and saponin compound. The test of these extract as antifungal is held by disk diffusion method with concentration variation of the extract is 50 %, 75%, and 100% (w/v). The extraction variation of the extract is implemented to inhibitory test and the result of the test to Candida albicans is 13,5 mm ; 16 mm ; 19 mm respectively and 12 mm ; 15 mm ; 17 mm to Pityrosporum . Base on the data ( zone diameter test of those fungal ) is concluded the extract of Aulbus Allium Cepa L. has a strong category inhibitory test. Keywords : Allium cepa, Candida albicans and Pityrosporum ovale